Tailoring the magnetic properties of cobalt ferrite nanoparticles using the polyol process - Bibani, Malek; Breitwieser, Romain; Aubert, Alex; Loyau, Vincent; Mercone, Silvana; Ammar, Souad; Mammeri, Fayna (Beilstein Journal of Nanotechnology, 2019)
Background: In extrinsically magnetoelectric materials made of two components, the direct magnetoelectric coupling arises from a mechanical strain transmission at the interface due to the shape change of the magnetostrictive component under an external magnetic field. Here, the size of the interface between the two components plays a crucial role. Therefore, the development of nanomaterials exhibiting large surface-to-volume ratios can help to respond to such a requirement. However, the magnetic nanoparticles (NPs) must be highly magnetostrictive and magnetically blocked at room temperature despite their nanometer-size. We describe here the use of the polyol process to synthesize cobalt ferrite (CoxFe3−xO4) nanoparticles with controlled size and composition and the study of the relationship between size and composition and the magnetic behavior.Methods: We used an improved synthesis of magnetostrictive CoxFe3−xO4 NPs based on the forced hydrolysis of metallic salts in a polyol solvent, varying the fraction x. Stoichiometric NPs (x = 1) are expected to be highly magnetostrictive while the sub-stoichiometric NPs (particularly for x ≈ 0.7) are expected to be less magnetostrictive but to present a higher magnetocrystalline anisotropy constant, as previously observed in bulk cobalt ferrites. To control the size of the NPs, in order to overcome the superparamagnetic limit, as well as their chemical composition, in order to get the desired magnetomechanic properties, we carried out the reactions for two nominal precursor contents (x = 1 and 0.67), using two different solvents, i.e., triethylene glycol (TriEG) and tetraethylene glycol (TetEG), and three different durations of refluxing (3, 6 and 15 h). The structure, microstructure and composition of the resulting NPs were then investigated by using X-ray diffraction (XRD), transmission electron microscopy (TEM) and X-ray fluorescence spectroscopy (XRF), respectively. The magnetic properties were also evaluated using standard magnetometry. To measure the magnetostrictive response of the particles, the particles were sintered to dense pellets on which strain gauges were bonded, measuring the size variation radially, as a function of a dc magnetic field.Findings: We found two samples, the first one being stoichiometric and magnetostrictive, and the second one being sub-stoichiometric and presenting a higher magnetization, that are appropriate to be used as ferromagnetic building blocks in nanostructured magnetoelectric materials, particularly materials based on polymers. We show that the polyol solvent and the reaction time are two key parameters to control the size and the magnetic properties of the resulting nanoparticles. We believe that these results provide relevant insights to the design of efficient magnetic and magnetostrictive nanoparticles that can be further functionalized by coupling agents, to be contacted with piezoelectric polymers.
Keywords: cobalt ferrite; magnetocrystalline anisotropy; magnetostriction; nanoparticle; non-stoichiometry; polyol process

(untitled) - Chu, Y.-H.; Martin, L. W.; Holcomb, M. B.; Gajek, M.; Han, S.-J.; He, Q.; Balke, N.; Yang, C.-H.; Lee, D.; Hu, W.; Zhan, Q.; Yang, P.-L.; et al. (Nat. Mater., 2008)

(untitled) - Wan, C.; Bowen, C. R. (J. Mater. Chem. A, 2017)

(untitled) - Onuta, T.-D.; Wang, Y.; Long, C. J.; Takeuchi, I. (Appl. Phys. Lett., 2011)

(untitled) - Andrew, J. S.; Starr, J. D.; Budi, M. A. K. (Scr. Mater., 2014)

(untitled) - Liu, R.; Zhao, Y.; Huang, R.; Zhao, Y.; Zhou, H. (J. Mater. Chem., 2010)

(untitled) - Zheng, H.; Wang, J.; Lofland, S.; Ma, Z.; Mohaddes-Ardabili, L.; Zhao, T.; Salamanca-Riba, L.; Shinde, S.; Ogale, S.; Bai, F.; Viehland, D.; Jia, Y.; et al. (Science, 2004)

(untitled) - Acevedo, U.; Lopez-Noda, R.; Breitwieser, R.; Calderon, F.; Ammar, S.; Valenzuela, R. (AIP Adv., 2017)

(untitled) - Liu, Y.; Xu, G.; Xie, Y.; Lv, H.; Huang, C.; Chen, Y.; Tong, Z.; Shi, J.; Xiong, R. (Ceram. Int., 2018)

(untitled) - Andrew, J. S.; Clarke, D. R. (Langmuir, 2008)

(untitled) - Martins, P.; Costa, C. M.; Benelmekki, M.; Botelho, G.; Lanceros-Méndez, S. (J. Mater. Sci., 2013)

Proceedings of the 21st IEEE Instrumentation and Measurement Technology Conference (IEEE Cat. No.04CH37510) - Affanni, A.; Guerra, A.; Dallagiovanna, L.; Chiorboli, G. (Design and characterization of magnetostrictive linear displacement sensors, 2004)

(untitled) - Bozorth, R. M.; Tilden, E. F.; Williams, A. J. (Phys. Rev., 1955)

(untitled) - Nlebedim, I. C.; Ranvah, N.; Williams, P. I.; Melikhov, Y.; Snyder, J. E.; Moses, A. J.; Jiles, D. C. (J. Magn. Magn. Mater., 2010)

(untitled) - Nlebedim, I. C.; Snyder, J. E.; Moses, A. J.; Jiles, D. C. (J. Magn. Magn. Mater., 2010)

(untitled) - Nlebedim, I. C.; Snyder, J. E.; Moses, A. J.; Jiles, D. C. (IEEE Trans. Magn., 2012)

(untitled) - Herrera, A. P.; Polo-Corrales, L.; Chavez, E.; Cabarcas-Bolivar, J.; Uwakweh, O. N. C.; Rinaldi, C. (J. Magn. Magn. Mater., 2013)

(untitled) - Repko, A.; Vejpravová, J.; Vacková, T.; Zákutná, D.; Nižňanský, D. (J. Magn. Magn. Mater., 2015)

(untitled) - Soler, M. A. G.; Lima, E. C. D.; da Silva, S. W.; Melo, T. F. O.; Pimenta, A. C. M.; Sinnecker, J. P.; Azevedo, R. B.; Garg, V. K.; Oliveira, A. C.; Novak, M. A.; Morais, P. C. (Langmuir, 2007)

(untitled) - Nakagomi, F.; da Silva, S. W.; Garg, V. K.; Oliveira, A. C.; Morais, P. C.; Franco Júnior, A.; Lima, E. C. D. (J. Appl. Phys., 2007)

(untitled) - Ammar, S.; Helfen, A.; Jouini, N.; Fiévet, F.; Rosenman, I.; Villain, F.; Molinié, P.; Danot, M. (J. Mater. Chem., 2001)

(untitled) - Mammeri, F.; Mamèche, F.; Kataya, Z.; Yaacoub, N.; Slawska-Waniewska, A.; Menguy, N.; Grenèche, J.-M.; Ammar, S. (MRS Online Proc. Libr., 2011)

(untitled) - Artus, M.; Ben Tahar, L.; Herbst, F.; Smiri, L.; Villain, F.; Yaacoub, N.; Grenèche, J.-M.; Ammar, S.; Fiévet, F. (J. Phys.: Condens. Matter, 2011)

(untitled) - Baldi, G.; Bonacchi, D.; Innocenti, C.; Lorenzi, G.; Sangregorio, C. (J. Magn. Magn. Mater., 2007)

(untitled) - Hyeon, T. (Chem. Commun., 2003)

(untitled) - Dai, Q.; Nelson, A. (Chem. Soc. Rev., 2010)

(untitled) - Lutterotti, L.; Matthies, S.; Wenk, H. R. (IUCr: Newsletter of the CPD, 1999)

(untitled) - Aragón, F. H.; Coaquira, J. A. H.; Villegas-Lelovsky, L.; da Silva, S. W.; Cesar, D. F.; Nagamine, L. C. C. M.; Cohen, R.; Menéndez-Proupin, E.; Morais, P. C. (J. Phys.: Condens. Matter, 2015)

(untitled) - Fiévet, F.; Ammar-Merah, S.; Brayner, R.; Chau, F.; Giraud, M.; Mammeri, F.; Peron, J.; Piquemal, J.-Y.; Sicard, L.; Viau, G. (Chem. Soc. Rev., 2018)

Des matériaux - Bailon, J. J.; Dorlot, L. M. (Ecole Polytechnique de Montréal, 1986)

(untitled) - Lu, R. E.; Chang, K. G.; Fu, B.; Shen, Y. J.; Xu, M. W.; Yang, S.; Song, X. P.; Liu, M.; Yang, Y. D. (J. Mater. Chem. C, 2014)

(untitled) - Ajroudi, L.; Mliki, N.; Bessais, L.; Madigou, V.; Villain, S.; Leroux, C. (Mater. Res. Bull., 2014)

(untitled) - Ourry, L.; Mammeri, F.; Toulemon, D.; Gaudisson, T.; Delamar, M.; Ammar, S. (RSC Adv., 2016)

(untitled) - Ourry, L.; Toulemon, D.; Ammar, S.; Mammeri, F. (Beilstein J. Nanotechnol., 2017)

(untitled) - Artus, M.; Ammar, S.; Sicard, L.; Piquemal, J.-Y.; Herbst, F.; Vaulay, M.-J.; Fiévet, F.; Richard, V. (Chem. Mater., 2008)

(untitled) - Gaudisson, T.; Artus, M.; Acevedo, U.; Herbst, F.; Nowak, S.; Valenzuela, R.; Ammar, S. (J. Magn. Magn. Mater., 2014)

(untitled) - Aubert, A.; Loyau, V.; Mazaleyrat, F.; LoBue, M. (J. Eur. Ceram. Soc., 2017)